Nano-scale analysis of synapse morphology in an autism mouse model with 15q11-13 copy number variation using focused ion beam milling and scanning electron microscopy. (29th October 2018) - Sato, Yuka; Okabe, Shigeo
Abstract : Nano-scale analysis of synapse morphology in an autism mouse model with 15q11-13 copy number variation using focused ion beam milling and scanning electron microscopy revealed relative increase in excitatory synapses with immature morphology but more astrocytic contacts, which may be linked to enhanced synapse turnover seen in ASD mouse models. Abstract: Circuit-level alternations in patients of autism spectrum disorder (ASD) is under active investigation and detailed characterization of synapse morphology in ASD model mice should be informative. We utilized focused ion beam milling and scanning electron microscopy (FIB-SEM) to obtain three-dimensional images of synapses in the layer 2/3 of the somatosensory cortex from a mouse model for ASD with human 15q11-13 chromosomal duplication (15q dup mice). We found a trend of higher spine density and a higher fraction of astrocytic contact with both spine and shaft synapses in 15q dup mice. Measurement of spine synapse structure indicated that the size of the post-synaptic density (PSD), spine head volume, spine head width and spine neck width were smaller in 15q dup mice. Categorization of spine synapses into five classes suggested a trend of less frequent mushroom spines in 15q dup mice. These results suggest relative increase in excitatory synapses with immature morphology but more astrocytic contacts in 15q dup mice, which may be linked to enhanced synapse turnover seen in ASD mouse models.